Methodik und Technik der Bestimmung struktureller Budgetdefizite - Gerhard Ziebarth (Deutsche Bundesbank, 1995)
When monitoring, interpreting and assessing budget policy decisions and developments, the public authorities' financial balance has always played a prominent role. The Maastricht Treaty on European Union and the provisions contained therein on budgetary criteria and reference values gave rise to an additional demand for informative and comparable budget indicators. The financial balance that can be taken from the various statistics is initially only a conglomerate collated to a single numerical variable from a combination of trend-related, cyclical and transitory external influences, on the one hand, and the interaction of basic fiscal policy decisions on the public receipts and expenditure system and discretionary measures of current budget policy, on the other. Different cyclical situations, in particular, often conceal or distort the picture of basic financial tendencies in public sector budgets.
Keywords: 330; Haushaltsdefizit; Volkswirtschaftliche Gesamtrechnung; Theorie; Deutschland